From Al-Kindi to Al-Attas: a journey through Muslim philosophy - Abdul Razak, Mohd Abbas; Artalim Zaim, Muntaha (Department of Communication, KIRKHS, IIUM, 2025)
The need for philosophy in the Muslim world is a highly contested issue. Those who oppose it argue that the Qur’an is sufficient and that Muslims should not rely on the philosophical ideas of the ancient world. On the other hand, those who recognize the beauty and benefit of engaging in philosophy advocate for its role in shaping the way we perceive and understand the natural world and the reason for our existence in this world. Historically, the development of philosophy in the Muslim caliphates began after the time of the Khulafāʾ al-Rāshidīn (633–661). As the Muslim empires expanded, their scholars came into close contact with the philosophical traditions of earlier civilizations such as the Greek, Persian, and Indian. The growth of philosophy as a vital and dynamic discipline reached its peak during the Abbasid period (750–1258), particularly in Baghdad. At the same time, a parallel intellectual flourishing occurred in Muslim Spain (711–1492), under a dynasty established by one of the surviving members of the Umayyad caliphate. Later, similar developments took place in Damascus and Cairo. These centers of learning actively participated in translating ancient manuscripts from various languages into Arabic, laying the foundation for a rich tradition of philosophical inquiry in the Muslim world.